2022
DOI: 10.3390/biom12060810
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Limitations of Stem Cell-Derived Beta Cells

Abstract: Great advances in type 1 diabetes (T1D) and type 2 diabetes (T2D) treatment have been made to this day. However, modern diabetes therapy based on insulin injections and cadaveric islets transplantation has many disadvantages. That is why researchers are developing new methods to regenerate the pancreatic hormone-producing cells in vitro. The most promising approach is the generation of stem cell-derived beta cells that could provide an unlimited source of insulin-secreting cells. Recent studies provide methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…It has been found that patients with diabetes mellitus and myocardial infarction have an increase in the level of endogenous malondialdehyde (MDA) and diene conjugates in the blood serum. The results obtained indicate the presence of oxidative stress in diabetes mellitus and myocardial infarction [6,7,8].…”
Section: Introductionmentioning
confidence: 70%
“…It has been found that patients with diabetes mellitus and myocardial infarction have an increase in the level of endogenous malondialdehyde (MDA) and diene conjugates in the blood serum. The results obtained indicate the presence of oxidative stress in diabetes mellitus and myocardial infarction [6,7,8].…”
Section: Introductionmentioning
confidence: 70%
“…modified the nutrients in the medium used for in vitro differentiation to further enhance generating functional SC-β-cells in vitro ( 52 ), and could also induce SC-β-cells by simulating the 3D culture system of human pancreatic development ( 53 ). In addition, Isaura ( 54 ) and Mariana ( 55 ) et al. recently updated and detailed the recent progress in using ESCs/iPSCs derived islet β-cells in vitro .…”
Section: β-Cell Replacement Options: Stem Cells and Porcine Isletsmentioning
confidence: 99%
“…In addition, the overall function of islet organoids is also defective compared to that of natural islets, such as the lack of an intact neurohumoral regulatory system and a synchronized, stable, and rapid insulin release from numerous β-cells based on it [ 124 ]. The defects in the overall function of islet organoids may also be associated with factors like the vascularization levels, the composition and arrangement of EC cells, and the heterogeneity of β-cells.…”
Section: Challenges In Construction and Application Of Islet Organoidmentioning
confidence: 99%